2022
DOI: 10.1186/s13023-021-02162-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Ceroid Lipofuscinosis Type 6 (CLN6) clinical findings and molecular diagnosis: Costa Rica’s experience

Abstract: Background Commonly known as Batten disease, the neuronal ceroid lipofuscinoses (NCLs) are a genetically heterogeneous group of rare pediatric lysosomal storage disorders characterized by the intracellular accumulation of autofluorescent material (known as lipofuscin), progressive neurodegeneration, and neurological symptoms. In 2002, a disease-causing NCL mutation in the CLN6 gene was identified (c.214G > T) in the Costa Rican population, but the frequency of this mutation among local Batte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This finding aligns with a study by Badilla-Porras et al in 2022, which described eight patients with CLN6 carrying the homozygous Costa Rican mutation. [26][27][28][29][30] MFSD8:p.(Tyr121Cysfs à 10) variant was presented in homozygosity and has not been previously reported in the literature. Mutations that lead to loss of function of the MFSD8 gene are classically described with the late infantile phenotype, characterized by seizures, progressive mental and motor deterioration, myoclonus, visual loss, and premature death, already widely described in the literature, with visual loss being a striking feature, presenting a variety of ophthalmological signs ranging from isolated macular degeneration to generalized retinopathy, depending on the genotype found.…”
Section: Discussionmentioning
confidence: 81%
“…This finding aligns with a study by Badilla-Porras et al in 2022, which described eight patients with CLN6 carrying the homozygous Costa Rican mutation. [26][27][28][29][30] MFSD8:p.(Tyr121Cysfs à 10) variant was presented in homozygosity and has not been previously reported in the literature. Mutations that lead to loss of function of the MFSD8 gene are classically described with the late infantile phenotype, characterized by seizures, progressive mental and motor deterioration, myoclonus, visual loss, and premature death, already widely described in the literature, with visual loss being a striking feature, presenting a variety of ophthalmological signs ranging from isolated macular degeneration to generalized retinopathy, depending on the genotype found.…”
Section: Discussionmentioning
confidence: 81%
“…This cohort had three sibling pairs with five females and four males. There were eight variants: seven of which had been previously reported, along with one novel variant (c.655 +1 G>A; IVS6+1) (Andrade et al, 2012; Badilla-Porras et al, 2022; Berkovic et al, 2019; Chin et al, 2019; White et al, 2018). Four subjects possessed homozygous variants: with two of those being siblings.…”
Section: Discussionmentioning
confidence: 99%
“…Previous neuroimaging studies of patients clinically-classified with vLINCL reported primary involvement of cortical and subcortical grey matter (Badilla-Porras et al, 2022;Baker et al, 2017;Cannelli et al, 2009;Guerreiro et al, 2013;Jadav et al, 2014;Petersen et al, 1996;Peña et al, 2001;Peña et al, 2004); however confirmed genetic diagnoses were not always established in these subjects, so the data could be representative of a mix of clinically-similar NCLs (Baker et al, 2017;Jadav et al, 2014). Recently, a few genetically-confirmed CLN6 cases were also reported to possess white matter signal abnormalities (WMSAs) (Guerreiro et al, 2013;Biswas et al, 2020;Cannelli et al, 2009;Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The CLN6 gene is located on chromosome 15q21-23, contains seven exons and encodes a protein with seven transmembrane domains, an N-terminal cytoplasmic domain and a lumen C-terminal. This protein is involved in endoplasmic reticulum-to-Golgi transfer of lysosomal enzymes, causing clinical symptoms[ 10 - 13 ].…”
Section: Discussionmentioning
confidence: 99%